Militancy in the Perspective of Industrial and Organizational Psychology - Endah Andriani Pratiwi; Shinta Febrina; Yoga Hardianto; Arief Budiarto (Borong Newinera Publisher, 2024)
Resilience in the face of change, adversity and uncertainty is an attitude that illustrates the spirit of militancy. The research team observed that there is no standard concept of militancy and its application in organizational life. The terms militant and militancy are often interpreted negatively in Indonesia, as they are associated with radicalism and terrorism (Purwastuti, 2011). In fact, in the Big Indonesian Dictionary (KBBI), militant means